[Rezension von: Baldus, Bernd, Origins of inequality in human societies] - Schwinn, Thomas (de Gruyter, 2020)
Rezension von: Baldus, Bern, Origins of inequality in human societies. New York/London: Routledge 2017, 250 S., gb., 136,45 € (kt. 50,49 €)
In: Soziologische Revue, 43 (2020), Nr. 3. pp. 400-405. ISSN 0343-4109 (Druck-Ausg.); 2196-7024 (Online-Ausg.)
Keywords: Rezension